Empowering Ghanaian communities to conserve their forests through a private-sector-led payment for ecosystem services mechanism - Nguyen, Phuong Minh; Talsma, Tiffany; Reymondin, Louis; Vantalon, Thibaud; Molina, Luis; Kyeretwie, Bram Nana Safo; Adzi, George Bush; Nguyen Perperidis, Emily (2025)
The Landscapes for Cocoa Livelihoods project reduced deforestation by 71% over 1,044 hectares in Ghana's Tano Offin Forest Reserve, conserving 6,911 tons of CO2 equivalent, 65,303 m³ of water recharge, and 39 hectares of biodiverse landscape over a period of 1 year (July 1st 2023 – June 30th 2024). This project demonstrates the scaling potential of a private-sector-funded Payment for Ecosystem Services (PES) model, where cacao-producing communities conserve the forest in exchange for collective rewards that improve every household’s living conditions.